Use of pumpless extracorporeal lung assist as rescue therapy in adolescent with cystic fibrosis - ÖZTÜRK, MAKBULE NİLÜFER (WILEY, 2013)
There is abundant evidence that artificial ventilation can aggravate pre-existing lung disease, which may contribute to morbidity and mortality. This is especially true for patients with air leakages. This case report describes the use of a pumpless extracorporeal lung assist as a rescue therapy to provide time to heal during the mechanical ventilation of a 16-year-old with cystic fibrosis who could not be managed via conventional means.
Keywords: cystic fibrosis; extracorporeal circulation; intensive care units; pediatric; RESPIRATORY-DISTRESS-SYNDROME; CARBON-DIOXIDE REMOVAL; INJURY